“Metodistas acolhem e cuidam”: análise dos fundamentos e práticas do acolhimento da Igreja Metodista aos (i)migrantes venezuelanos no Brasil - Nascimento, Fabio Fonseca do (2021)
This research aimed to analyze the practical actions of welcoming from the Methodist Church to the Venezuelan immigrants in Brazil, bringing as a framework of theoretical understanding the references of Wesleyan theology and, also, some authors from the decolonial perspective. To accomplish this task, we used the Ver-Julgar-Agir (See-Judge-Act) methodology as a contribution to the analysis of each chapter. With the Ver (see) method, we identified elements that characterize the humanitarian crisis in Venezuela, which led to the massive migration of the Venezuelan population to neighboring countries in Latin America in the late 2010s. In this sense, the Venezuelan historical context of the end of the century XX was initially studied, and beginning of the XXI century that caused the immigration of the Venezuelan population to other countries and considered, for this purpose, the theoretical contribution of authors working on transnational migrations in Latin America, to reflect the migratory movements generated by the political, social and economic crisis. that Venezuela has been experiencing. In addition to the social, historical and economic aspects, this work was supported by principles of Wesleyan social theology that underpin the Church's solidarity actions, in which the engaged theology that is intrinsically associated with its practical life stands out. For this analysis, we considered the Julgar (judge) method from the Christological perspective. Salvation as a means of grace in Wesley, aroused social commitment to the marginalized population of England in the eighteen century and continues to provide the basis for the social responsibility actions that the Church takes in its surroundings on the contemporary scene. However, from the field research, which involved interviews through a digital platform with the participation of the Methodist Churches of Boa Vista / RR, Methodist of Luz/SP, Secretariat for Life and Mission departament of the national area of the Church, and a lay member of the Methodist Church who acted and act directly and indirectly in Programs and actions to welcome Venezuelan immigrants, we perceive some ambiguities that involve the distance between the theological proposal for social commitment and practices and discourses of the Methodist Church in relation to immigrants who denote a gaze still permeated by colonialist logics. More specifically, we analyzed the narratives from the methodological aspect Agir (act). In this sense, as a result, we can identify that, although the work of welcoming the Methodist Church to the Venezuelan immigrants is within the perspective of solidarity actions and social responsibility indicated in Wesleyan theology and in the documents that drive the mission of the Methodist Church. Some divergences between the theoretical and practical perspectives were pointed out in the speeches of the people interviewed, with regard to the mission of the Methodist Church.